Epidemiology of Healthcare-Associated Infections, Coused by Sapronoses Group Pathogens - E. B. Brusina (Эпидемиология и вакцинопрофилактика)
Sapronoses group pathogens are characterized by highly epidemic features and play a significant role in healthcare-associated infections (HAIs). They can be responsible for outbreaks and severe infections with high mortality and disability of patients. Their share in the etiological structure of HAIs reaches 30%. The most actual sapronoses group pathogens causing HAIs includes Legionella spp., Pseudomonas spp., Serratia spp. and Clostridium spp. The article discusses the taxonomy, ecology pathogenicity factors and reservoir, particularly sources of infection, factors and ways of pathogens transmission in healthcare settings. The prevention and control measures are systematized.